CHRONIC PELVIC COMPLAINTS IN FEMALES WITH IRRITABLE BOWEL SYNDROME: ANOTHER BURDEN TO DEAL WITH - Georgescu Doina; Georgescu Liviu-Andrei (European Scientific Journal, ESJ, 2014)
Introduction: Pain is ubiquitarium in patients with irritable bowel syndrome (IBS) being associated with diminished quality of life. Aim: comparing effectiveness of gabapentin high dose versus gabapentin half dose plus probiotics and dimeticone in mitigating the pelvic complaints in female patients with IBS . Methods: Open label random clinical study of 30 female patients, mean age= 38,76±15,51 years, diagnosed with predominant constipation IBS, according to Rome III criteria, suffering from chronic pelvic complaints were enrolled after ruling out other causes of pelvic symptoms. Intensity of dyspareunia, cystalgia, urinary urge were scored according to Likert scale from 0 = no symptoms to 6 = very severe. Patients were randomly devised in 2 groups, each of 15 patients. First group received gabapentinum in dose of 1200 mg/day, the second group received Gabapentin 600mg/day associated with probiotics (1 billion strains/ capsule Lactobacillus acidophilus 50% and Bifidobacterium bifidus 50% ),3 capsules/day plus dimeticone 80 mg, 3x2 chewing pills/day for 3 months. Results: First group had the following scoring : prior therapy dyspareunia =2,93±0,88. cystalgia =3±1,31, urinary urge =2,58±1,25; after therapy: dyspareunia= 2,20 ±0,77 (p=0,0022),cystalgia =2,2±0,86 (p=0,058),urinary urge =2,07±0,73 (p=0,26).Second group had the following scoring prior therapy: dyspareunia =3,13±1,06, cystalgia =2,73±1,16.urinary urge =1,87±1,13; after treatment: dyspareunia =1,6±0,63 (p<0,0001), cystalgia =1,40±0,50 (p=0,0003), urinary urge =0,66±0,61 (p=0,0011). Conclusions: Gabapentin in high dose monotherapy was significantly efficient only for mitigating dyspareunia. Association with probiotics and dimeticone to gabapentin half doses resulted in an increased response and all the assessed complaints were significantly alleviated.